Análise de diferentes configurações do leito de jorro com agitador mecânico e do equipamento convencional - Barros, João Pedro Alves de Azevedo (Universidade Federal de São Carlos, 2022)
The mechanical spouted bed emerged as a modification of the conventional spouted bed to minimize problems in the movement of solids and the need for high air flows just for the existence of the spouting regimen. Therefore, this study aimed to analyze the modified spouted bed configurations incorporating three different types of the mechanical stirrer, and to observe the differences relative to the conventional equipment. Straight-blade, inclined-blade, and helical screw agitators were used with different types of inert particles (glass, alumina and polyethylene). For the analysis, variables such as the fluid dynamic behavior, velocity profile, air flow reduction, cycle time, drying and granulometry. The fluid dynamics of the mechanical spouted bed depends on the geometry of the stirrer and its speed of rotational. In the agitators with the form of straight or inclined-blades, the fluid dynamics was qualitatively similar to the conventional spouted bed, however, the differences between the conventional and the agitated bed become significant as the rotation speed of the agitator increases. For example, as a result of the increase in the rotation of the stirrer, there is a reduction in the fluid dynamic parameters, mainly in relation to the air flow required to agitate the bed. Similarly, the air velocity profile will also depend on the type of stirrer, the air flow used and the rotation speed, with higher values in the center of the bed, except for the screw-type stirrer. The effects of rotation speed and blade inclination on fluid dynamics were minimized from 240 rpm, depending on the mass of the particles inside the bed. The inclined-blade stirrer showed the best reduction in airflow and pressure drop, considering the effect of rotation speed and the different groups of particles, mainly in the tests with a greater height of the static bed. The increasing in the number of stirrer blades resulted in reduced air flow and better bed stability, but these results were only more evident at low rotational speeds. The proposed model for the straight-blade stirrer provided good predictions in terms of maximum pressure drop and air flow. In the drying process, it was evident that the time to reach equilibrium was different for each of the configurations, that is, the changes caused a change in the transient regime of the drying process. Rotation speed is also a parameter that can control the drying process, which also affects the characteristics of the final product, such as moisture and granulometric distribution. In general, the use of stirrers in the spouted bed provided significant improvements, reducing the air flow needed to stirrer the bed and pressure drop, in addition to providing greater stability to the bed. The XVII insertion of the stirrer in the bed can favor new applications and also expand the operating ranges of the conventional spouting, since in this equipment there are no problems of spout collapse and geometric limits.
Analysis of different configurations of the spouted bed with a mechanical stirrer and conventional equipment
Keywords: Fluidodinâmica; Secagem; Leito de jorro; Agitador mecânico; Fluid dynamics; Drying; Spout bed; Mechanical stirrer; ENGENHARIAS::ENGENHARIA QUIMICA::OPERACOES INDUSTRIAIS E EQUIPAMENTOS PARA ENGENHARIA QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA